Analysis of the Film "Kukira Kau Rumah" as a Media for Mental Health Introduction - Rafiadi, Arrest Bupala; Nugraha, Raffi Febriansyah; Nurfalah, Farida (Journal of Comprehensive Science, 2025)
Mental health is an important aspect of an individual's life, especially adolescents that adolescence is a crucial stage of emotional and sociocognitive development. Bipolar mental health disorder is a serious psychological problem caused by an imbalance of neurotransmitters in the brain. Sufferers experience extreme mood swings, and if they get worse, they can become depressed. The purpose of this research is to reveal the way mental health is portrayed in film works, as well as how its role provides understanding to the public. The research method used is a qualitative method. This study uses data collection in the form of interviews and documentation. The results show that the film has managed to foster empathy and public understanding of the importance of mental health, although the medical explanation of bipolar is still lacking. This film plays a role in challenging social stigma, building collective awareness, and encouraging openness to psychological issues in society.